Subsistence lives! - Khumbane, Tshepo (Technical Centre for Agricultural and Rural Cooperation, 2001)
In a world used to thinking in terms of historical epochs and timelines, South Africa is supposed to have made a clean break from its world-infamous apartheid rule. The truth is, the past of 'New' South Africa is still very much alive. It has to do...